VARIOUS VEGETATION MODIFIES THE DIVERSITY OF HERPETOFAUNA IN WONOSOBO AGRICULTURAL LANDSCAPE - Nia Kurniawan; Bagyo Yanuwiadi; Bagus Priambodo; Andri Maulidi; Agung Sih Kurnianto (Journal of Environmental Engineering and Sustainable Technology, 2017)
Human population growth has rapidly conversed the natural environment into agricultural and plantation area in Indonesia. This phenomenon resulted a reduction and fragmentation habitats, and led to the loss of biodiversity. By exploring Wonosobo, we were able to analyse the herpetofauna composition on three different habitat, including river, salak plantation [Salacca zalacca (Gaert.) Voss], and paddy fields. We identified 17 species (60,7%) from river, 15 species (53,6%) from paddy field, and 13 species (46,4%) from salak plantation. Shannon-wiener index diversity (H’) categorized herpetofauna diversity in all three habitats as medium. Meanwhile, the evenness index (E) showed that herpetofauna community in river classified as unstabile (E=0.7302). River was predicted be functioned as transit area for herpetofauna to hunt. There were no herpetofauna species predominating all three habitats, and this indicating that the ecosystem balance was well preserved. This study revealed that agriculture and plantation area affected the herpetofauna composition, yet it still able to maintain the diversity well. In addition, the water bodies, including river and irrigation in agriculture and plantation area, should be maintained its quality as it plays an important part in herpetofauna conservation. Keywords: fragmentation, herpetofauna composition, habitat